Revisiting the role of IL-27 in obesity-related metabolic diseases: safeguard or perturbation? - An, Jinyang; Fu, Donghua; Chen, Ximei; Guan, Conghui; Li, Lingling; Bai, Jia; Lv, Haihong (Frontiers in Immunology, 2025)
The prevalence of metabolic diseases, such as obesity, has been steadily increasing in recent years, posing a significant threat to public health. Therefore, early identification and intervention play a crucial role. With the deepening understanding of the etiology of metabolic diseases, novel therapeutic targets are emerging for the treatment of obesity, lipid metabolism disorders, cardiovascular and cerebrovascular diseases, glucose metabolism disorders, and other related metabolic conditions. IL-27, as a multi-potent cytokine, holds great promise as a potential candidate target in this regard. This article provides a comprehensive review of the latest findings on IL-27 expression and signal transduction in the regulation of immune inflammatory cells, as well as its implications in obesity and other related metabolic diseases. Furthermore, it explores the potential of IL-27 as a novel therapeutic target for the treatment of obesity and metabolic disorders. Finally, an overview is presented on both the opportunities and challenges associated with targeting IL-27 for therapeutic interventions.